2001
DOI: 10.1074/jbc.m104342200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Chimeric Reverse Transcriptases with Polypeptide Subunits of Highly Divergent HIV-1 Group M and O Strains

Abstract: Human immunodeficiency virus (HIV)-Lys -primed HIV-1 genomic RNA. These findings suggest that the initiation event is conserved between HIV-1 groups, but not HIV types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 47 publications
1
51
0
Order By: Relevance
“…The increased sensitivity of the mutant enzymes to the denaturing (inactivating) effect of urea is due to an easier conversion of the mutant (heterodimeric) enzymes to their monomeric state, rather than to easier unfolding of their secondary structure by urea. Indeed, SluisCremer et al [24] and Menéndez-Arias et al [12] have shown that urea at concentrations less than 2 M (as is the case in our experiments) results in a decreased catalytic activity of the RT enzyme due to dissociation of the heterodimer to monomers, and not to destruction (unfolding) of the secondary structure of the enzyme (which occurs at higher urea concentrations). Our observations are also in agreement with earlier published results that focus on the importance of an intact b7-b8 loop in the p51 subunit to retain efficient catalytic activity of the enzyme [10,11].…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The increased sensitivity of the mutant enzymes to the denaturing (inactivating) effect of urea is due to an easier conversion of the mutant (heterodimeric) enzymes to their monomeric state, rather than to easier unfolding of their secondary structure by urea. Indeed, SluisCremer et al [24] and Menéndez-Arias et al [12] have shown that urea at concentrations less than 2 M (as is the case in our experiments) results in a decreased catalytic activity of the RT enzyme due to dissociation of the heterodimer to monomers, and not to destruction (unfolding) of the secondary structure of the enzyme (which occurs at higher urea concentrations). Our observations are also in agreement with earlier published results that focus on the importance of an intact b7-b8 loop in the p51 subunit to retain efficient catalytic activity of the enzyme [10,11].…”
Section: Discussionmentioning
confidence: 86%
“…For determination of the 50% inhibitory concentration (IC 50 ) of the test compounds against HIV-1 RT, the RNA-dependent DNA polymerase assay was performed as follows: the reaction mixture (50 ll) contained 50 mM Tris-HCl (pH 7.8), 0.06% Triton X-100, 5 mM DTT, 0.3 mM glutathione, 150 mM KCl, 5 mM MgCl 2 , 1.25 mg/ml BSA, 0.5 mM EDTA, 0.1 mM template/primer poly(rC)AEoligo(dG) [12][13][14][15][16][17][18] (Amersham Biosciences), a fixed concentration of the labeled substrate [8-3 H]dGTP (1.6 lM, 1 lCi; specific activity, 12.6 Ci/mmol; Amersham Biosciences), 5 ll of inhibitor solution [containing various concentrations (10-fold dilutions) of the compounds], and 5 ll of the RT preparations. In the case, where d4TTP (or PFA) were evaluated for their inhibitory activity, 0.15 mM poly(rA)AEoligo(dT) [12][13][14][15][16][17][18] was used as the template/primer, and 1.6 lM [ 3 H]dTTP as the radiolabeled substrate.…”
Section: Reverse Transcriptase Assaymentioning
confidence: 99%
See 3 more Smart Citations